A Gravity Model Analysis of China’s Trade in Renewable Energy Goods With ASEAN Countries as Well as Japan and South Korea - Zhang, Wei; Yu, Kaiyi; Fang, Yingying (Frontiers in Environmental Science, 2022)
Focusing on the components of both solar photovoltaic technology and wind energy technology and using the gravity model approach with panel data, this study empirically investigated the determinants of bilateral trade in renewable energy goods among ASEAN countries as well as with China, Japan, and South Korea for the period 2012–2019, and also identified China’s export efficiency and export potential. The results showed that the economic sizes of both the exporting and importing countries, the economic freedom of the exporter, and trade agreements and membership of common trade areas significantly encouraged bilateral trade, while geographical distance exerted a significantly negative influence. In general, it was found that China had great potential to export renewable energy goods. We propose that the ASEAN Plus Three region needs to formulate and implement a comprehensive and carefully coordinated renewable energy policy package. We also suggest that China should promote joint efforts with ASEAN, Japan and South Korea to further deepen cooperation on the low-carbon economy and tap the great potential for trade in renewable energy goods.